ε-Isometries of convex bodies in l^n_∞ and l^n_1 - Vestfrid, Igor A. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 It is shown that every ε-isometry of a convex body in l^n_∞ or in l^n_1 can be well approximated by an affine surjective isometry.